Role of Urodynamic Study in the Management of Pelvic Organ Prolapse in Women - Daneshpajooh, Azar; Mirzaei, Mahboubeh; Dehesh, Tania (Urology Journal, 2021)
Objectives: Pelvic organ prolapse (POP) and lower urinary tract symptoms (LUTS) usually coexist and are common among women. Since the efficacy of urodynamic studies (UDS) in evaluating these conditions is subject to controversy, this study aimed to assess the accordance between urodynamic findings and LUTS and to determine the importance of UDS in women with POP. Methods: This cross-sectional study was conducted on women over 18 years with symptomatic POP referred to the female urology clinic of Kerman University of Medical Sciences, Kerman, Iran, during 2017-2018. Patients who met the inclusion criteria were included in the study with informed consent. The Pelvic Floor Disability Index (PFDI-20) was completed for each patient. Pelvic examination was performed using the Pelvic Organ Prolapse Quantification System (POPQ). Subsequently, multi-channel UDS was performed, and the findings were analyzed in SPSS 20, using Chi-square or Fisher’s test. Results: A total of 200 women with symptomatic POP were included in the study. Stress, urge, and mixed urinary incontinence showed significant accordance with the urodynamic findings (urodynamic stress incontinence and/or detrusor overactivity). However, there was no significant relationship between urinary voiding LUTS and urodynamic findings. Conclusion: UDS should be performed for selective patients with POP. According to the results of the present study, UDS can help us provide consultation for POP patients with voiding LUTS. However, in POP patients with urinary incontinence, this test cannot provide further information and should be performed based on the patient’s condition.